The evidence for Jesus - Dunn, James Douglas Grant, 1939- (Louisville, KT Westminster, 1985)
Includes bibliographical references and index.
Keywords: Bible. N.T. Gospels -- criticism, interpretation, etc; Jesus Christ -- historicity; Jesus Christ -- person and offices